Nutritional status and its association with constipation in spastic cerebral palsy - Awan, Waqar Ahmed; Masood, Tahir; Kanwal, Raheela (Pakistan Journal of Physiology, 2019)
Background: In Cerebral Palsy (CP) bowel dysfunction is very common. As a result of the pelvic autonomic dysfunction, constipation becomes one of its clinical manifestations. The objective of this study was to determine the association of nutritional status and spasticity with constipation in CP children. Methods: Sixty children with spastic CP on oral feeding with constipation between ages 2–12 years of both genders, spasticity score above 1+ grade on modified Ashworth scale of spasticity, functional activity level between 2–5 grades on gross motor functional classification scale were included. Along with demographic detail defecation frequency and constipation severity through constipation assessment scale was documented. To calculate average nutritional status, fluid and meal history for the last three days was taken from parents. Pearson product-moment correlation coefficient was used to find association between continuous variables and chi-square test was used for categorical variables. Results: Spasticity showed significant association with defecation frequency (p<0.001) and inability to pass stool (p<0.001). The spastic CP children had on average low nutritional intake. Low sodium intake was negatively associated with rectal pain during defecation (p=0.04) and overall constipation severity (p=0.03). Low monounsaturated fats and sugar was also negatively associated with inability to pass stool (p=0.04) and oozing of stool in spastic CP children (p=0.03), respectively. Conclusions: Spasticity was negatively associated with the defecation frequency in CP children. Increased monounsaturated fat intake may reduce difficulty in passing stool, increase sugar intake could reduce oozing of stool and increase sodium intake could reduce rectal pain and constipation severity.